1979
DOI: 10.2503/jjshs.48.73
|View full text |Cite
|
Sign up to set email alerts
|

Salt Tolerance of Tomatoes

Abstract: Experiments were conducted to determine the effect of diluted sea water on the germination, growth and yield of tomatoes. 1) The germination percentage of tomato seeds decreased even at 100 ppm Cl 2 days after the test was started. The germination percentage in 6 days was not significantly different among 0 to 1000 ppm Cl. Yet, germination at 2000 and 3000 ppm Cl was 80.5 and 21.5%, respectively, and was significantly lower than among 0 to 1000 ppm Cl. 2) Transpiration rate of tomatoes transferred to diluted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In addition, Bernstein et al (1974) reported that yield reduced by 50% under saline soil(8 ds m -1 ). Similar results were obtained by Nukaya et al (1979) who reported that tomato was irrigated with saline water (50 -3000 ppm) the yield reduced by 47%. Rajasekaran and Shanmugavelu (1981) and Mondal (1983) reported reduction in tomato yield that was grown under irrigation with saline water ranged from 2.8 to 10.2 ds m -1 , the reduction ranged from 5 to 40%.…”
Section: Resultssupporting
confidence: 88%
“…In addition, Bernstein et al (1974) reported that yield reduced by 50% under saline soil(8 ds m -1 ). Similar results were obtained by Nukaya et al (1979) who reported that tomato was irrigated with saline water (50 -3000 ppm) the yield reduced by 47%. Rajasekaran and Shanmugavelu (1981) and Mondal (1983) reported reduction in tomato yield that was grown under irrigation with saline water ranged from 2.8 to 10.2 ds m -1 , the reduction ranged from 5 to 40%.…”
Section: Resultssupporting
confidence: 88%
“…In the present work, plants usually were shorter at the higher salt concentrations, but some authors say that plant growth may increase slightly following treatment with low concentrations of NaCl (Nukaya et al,, 1979;Shannon et al, 1987).…”
Section: Discussionmentioning
confidence: 47%
“…Common effects of salinity are in inhibition of germination, stunting of growth, chlorosis on leaves and depression of yields (10,11).…”
Section: Discussionmentioning
confidence: 99%